Freight in a Bicycle-Friendly City: Exploratory Analysis with New York City Open Data. Issue 1 (2016) - Conway, Alison; Tavernier, Nathan; Leal-Tavares, Victor; Gharamani, Niloofar; Chauvet, Lisa; Chiu, Medwin; Bing Yeap, Xue
This project employs a variety of open data sets to examine how New York City's growing bicycle infrastructure has had an impact on travel and parking conditions for commercial vehicles (CVs), and to investigate the interactions that occur between CVs and bicycles on multimodal urban streets. The project was conducted in three stages. First, a spatial analysis of the city's dedicated bicycle and local truck routes was performed to quantify the extent of network overlap and changes that have occurred since 2000. Next, a spatial and statistical analysis of bicycle collisions extracted from the New York Police Department's motor vehicle collision database was conducted to explore infrastructure and demand characteristics indicative of freight–bicycle conflicts. Finally, CV–bicycle lane parking violations were extracted from a New York City Department of Finance's parking violation database to examine parking challenges in bicycle-friendly areas; field data were also collection in three critical locations. The project identified several challenges for CV operations. Potential future research efforts to address emerging questions requiring further investigation are also discussed.